New Developments in Understanding the Histological Structure of Human Ear Cartilage - Kaňa, M; Kaňa, R; Povýšil, C (Folia biologica, 2019)
Histological, immunohistochemical and molecular examination of bioptic samples of 30 normal adult auricular cartilages and small samples from 6 ear cartilages from aborted foetuses was performed. The adult cartilage was the tissue with minimal proliferative activity, which we were able to confirm with antibodies against Ki67 in contrast to a high proliferative activity in the auricular cartilage of foetal tissues. It may therefore be presumed that the process of foetal tissue maturation is undoubtedly associated with a significant reduction in proliferative activity. The mature lamella of the adult auricular cartilage has a histological tri-lamellar structure. There are a great number of elastic fibres in the intercellular matrix of the central zone, which are conversely present in only small amounts in both peripheral layers. While the external layer of the concave surface of the cartilage contains a fewer number of oval elements, the external layer of the convex side is composed of numerous fusiform chondrocytes. Antibodies against various subtypes of S-100 protein showed that auricular chondrocyte activity is modified depending on the configuration of individual distinct zones (isoforms A1, A6, B2 and P were positive in all layers, isoforms A2 and A2 in peripheral zones). The most active cells metabolically are most likely chondrocytes in both external layers adjacent to the perichondrium. We have also demonstrated α-smooth muscle actin (SMA)-positive chondrocytes in both peripheral layers of the auricular cartilage adjacent to the perichondrium. In addition, we found definite differences in the distribution of actin-positive cells depending on the external shape of the pinna. The majority of these fusiform cells were localised primarily in the areas of great curvature of the pinna, especially the convex side, as mentioned above. On the basis of these unique structural features we assume that the ear cartilage may embody an example of the socalled intelligent biological material, which has its internal structure made in such a way as to more easily develop and yet still maintain all the shape characteristics of the human auricle. The knowledge of these specific structural characteristics is important especially for use of auricular cartilage in auricular reconstruction.
Keywords: imunohistochemie; dospělí; Postmortem Changes; plod; proteiny S100; Ear Cartilage; Immunohistochemistry; lidé; S100 Proteins; Fetus; ušní chrupavka; Adult; posmrtné změny; Humans